Encouraging On-Time Completion of Leprosy Patients Treatment: Implementing E-Leprosy Framework to Primary Health Care in Indonesia. (May 2019) - Rachmani, Enny; Hsu, Chien-Yeh; Chang, Peter W. S.; Jumanto, Jumanto; Fuad, Anis; Ningrum, Dina N. A.; Yeh, Chih-Yang; Lin, Ming-Chin
Low adherence to leprosy treatment is the main challenge in Indonesia. This is a quasi-experimental observational study in a real setting of a leprosy control program in Indonesia. The study is aimed at evaluating an e-leprosy framework in increasing the rate of on-time attendance at primary health care and on-time completion of treatment of leprosy patients. This study has implemented an e-leprosy framework for primary health care at Pekalongan District. The intervention was conducted for 19 months to observe a 1-episode long-term treatment of leprosy patients. The study collected data of 391 registered patients from June 2012 to March 2016. Based on the inclusion and exclusion criteria, this study selected 188 patients. The SMS (short message service) reminders proved to be effective in increasing on-time completion and on-time attendance rates by 21% and 14.6%, respectively. There is a trend for late collections of the drugs at the 3rd, 8th, and 11th multidrug therapy drug collections.